ANALISIS MINAT BACA BUKU PADA PESERTA DIDIK KELAS IV DI MIN 1 SIDOARJO - Siti Shofiyah; Muhammad Dwi Santoso; Jazilah Rohmatika; Sihabudin; Imroatul Mufidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Reading activities are part of education, but the reality in the field shows that students tend to be lazy when asked to read books. This is because there are internal factors that come from oneself and external factors that come from outside. This research aims to analyze the level of interest in reading books, factors that influence interest in reading books and teachers' efforts to increase students' interest in reading books. This research is a survey with descriptive analysis using a combination approach, namely qualitative and quantitative. Data collection techniques using interview and questionnaire methods are given to students. The subjects of this research were class IV students at MIN 1 Sidoarjo with a total of 29 students. The research results show that the reading interest of class IV students at Min 1 Sidoarjo is in the good category with a percentage of 77.9. There are internal and external factors that influence students' reading interest. Teachers have tried to increase students' interest in reading by getting used to reading activities before learning takes place and motivating students about the importance of reading books